2022
DOI: 10.1186/s12968-022-00868-y
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function declines prior to left ventricular ejection fraction in hypertrophic cardiomyopathy

Abstract: Background The right ventricle (RV) in hypertrophic cardiomyopathy (HCM) tends to be neglected, as previous efforts have predominantly focused on examining the prognostic value of left ventricular (LV) abnormalities. The objectives of this study were to assess RV function in HCM, changes over time, and association with clinical outcomes. Methods Two hundred and ninety HCM patients with preserved LV ejection fraction (LVEF ≥ 55%) and 30 age- and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…First, this study focused on HCM with preserved LVEF in hospitalized patients. Therefore, the percentage of HCM patients with LGE (82.81%) and LVOTO (65.63%) was high compared with a prior study that focused on all HCM patients with preserved LVEF ( 16 ). Such an approach helped us learn more accurately about more serious HCM patients of this subtype, thus promoting their clinical management.…”
Section: Discussionmentioning
confidence: 81%
“…First, this study focused on HCM with preserved LVEF in hospitalized patients. Therefore, the percentage of HCM patients with LGE (82.81%) and LVOTO (65.63%) was high compared with a prior study that focused on all HCM patients with preserved LVEF ( 16 ). Such an approach helped us learn more accurately about more serious HCM patients of this subtype, thus promoting their clinical management.…”
Section: Discussionmentioning
confidence: 81%
“…Such changes have significantly higher predictive values than conventional parameters. For example, Mahmod et al [22] found that both RV and LV strain were impaired in patients with HCM despite normal LVEFd. A small decrease was observed in RVEF, but it was within the acceptable normal range.…”
Section: Discussionmentioning
confidence: 99%
“…The information obtained from CMR is presented in Table 2 (Ref. [2,[10][11][12][13][14][15][16][17][18][19][20][21][22]). Our study included ten prospective studies [2,[10][11][12]14,15,[18][19][20][21] and four retrospective studies [13,16,17,22].…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations